Implementasi Metode Incremental Dalam Membangun Sistem Informasi Administrasi Paroki santa Maria diangkat Ke Surga Eban - severinus ponis; Yoseph P. K. Kelen; Krisantus J. Tey Seran (Journal of Informatics and Computing, 2023)
The Parish of Santa Maria Was Appointed To Heaven Eban is one of the parishes which was inaugurated on March 23, 1952 by the Apostolic Vicariate of Atambua-Timor. This parish is located in West Miomaffo, North Central Timor District, East Nusa Tenggara Province, with around 12,000 parishioners spread across 23 neighborhoods. Service activities provided by the Parish Priest are recorded and stored by the Parish Secretariat partially manually and partially using a computer application. The data processing system used does not yet have a database stored on a computer, so if a church or congregation needs information, each file must be checked one by one to obtain the data needed. So it will take a long time in the search process. Based on these problems, a website-based Parish Administration Information System (SIAP) is needed so that it can provide better service in conveying existing information. SIAP is expected to be able to manage administrative data such as registration for Sacrament Services. The sacraments served are Baptism, First Communion, Confirmation and the Sacrament of Marriage. SIAP development uses the Incremental system development model. The reason for using this method is because this method is considered to be able to accommodate changes flexibly and has a lower risk to the system development process.